Socio-Scientific Issues (SSI) Approach Implementation to Enhance Students' Creative Thinking Skills: Literature Review - Gumilar, Panji; Djono; Umuda, Aghilatul; Sari, Diah Ayu Puspita; Abidin, Nur Lailatul Fitriyah (Universitas Sebelas Maret, 2025)
Creative thinking skills are one of the 21st-century skills that students must possess. This study aims to analyze the implementation of the Socio-Scientific Issues (SSI) approach to improve students' creative thinking skills. The study identified gaps between textbook content and actual student misconceptions in the Indonesian context. The research method used a literature review of scientific articles that align with the research objectives. Scientific articles were sorted using the Publish or Perish (PoP) application version 8 and selected based on the publication period between January 2021 and December 2025, published in journals indexed by Sinta 1 and Sinta 5 and not as a literature review. Three articles were obtained that met the selection criteria and met the article quality assessment. The results of the study indicate that there is a positive impact of implementing the SSI approach on improving students' creative thinking skills. The subject matter taught includes environmental change and conservation as well as green chemistry. The SSI approach can be applied to various learning models, namely Interactive Socio-Scientific Inquiry (ISSI), Problem-Based Learning (PBL), and Project-Based Learning (PjBL).